New Urbanism in Europe and the USA: National schools - Kopylova, Larisa (project baikal, 2023)
The article discusses the main ideas of New Urbanism, an urban development movement that has existed since the 1980s and is close to the principles of a traditional city. The spread of these ideas is shown on the example of national schools in Europe and the USA. The responses of the architects of New Urbanism to such challenges of modern civilization as post-industrialism, ecological crisis, destruction of historical cities are analyzed. An aesthetic and semiotic assessment of the role of order and vernacular architecture in a modern traditional city is given. Differences and intersections in the national schools of the USA, England, France, Italy, Holland and others are traced.
Keywords: New Urbanism; traditional citу; vernacular; order; L. Krier; A. Duany; E. Plater-Zyberk; P. Bontempi; Q. Terry